A mediação da informação de interesse policial: um estudo sobre o planejamento da PMPA no desenvolvimento de ações preventivas - SANTOS, Luana Suelen Pacheco dos (2018)
Contemporary society, also called the information society, is marked by instantaneous changes in what concerns the informational explosion, and information is an anchor point in the search for the solution of the most varied problems. In the sphere of Public Security, the use of information is one of the central elements in the development of strategies to combat and combat crime. In order to make use of the information in the planning of preventive actions to combat violence, first of all it is necessary to have this range of information organized, which requires mechanisms that enable the production of knowledge. In this sense, this study evidences the mediation of public security information, which allows the management and use of information in order to systematize the information generated in the Integrated Public Security System (SISP) database. The use of information for the sake of public safety allows the creation of a systematic process of knowledge production, since the indicators derived from criminal statistics help in the elaboration of actions to fight crime, allowing society to feel safer, which is also directly related to a significant change in the way military police officers operate, evidencing characteristics such as intelligence and proactivity.